Demonstration of geographic information system based description of responsive and sensory qualities of two civic nodes of Calcutta - Das, Subhrendu (Kansas State University, 2006)
Sensory qualities of a place are those that help people perceive a place through their senses (Lynch 1976). Responsiveness of a place is its ability to provide the user with a wide range of choices and opportunities (Bentley et al 1985). This thesis demonstrates a study of sensory and responsive qualities of urban spaces through the description of two civic nodes in the city of Calcutta, India – the Dalhousie Square and the Salt Lake City Center. The demonstration technique adopted for the study uses Geographic Information System. This system, with the help of specialized computer software can manipulate, summarize, query, edit and visualize geographic information stored in a database. In this study site observations on the two civic nodes are presented as layers of information in Geographic Information System. The civic nodes selected for this study were built at different times. The Dalhousie Square is the historic city center of the city of Calcutta, built during the British rule (1776-1947) over India. The Salt Lake City Center is a mixed-use retail development designed by the Indian architect Charles Correa.
Keywords: Civic Nodes of Calcutta; Architecture (0729)